A systematic review of learning curves in plastic and reconstructive surgery procedures - Tapking, Christian; Kowalewski, Karl-Friedrich; Hundeshagen, Gabriel; Kneser, Ulrich; Hirche, Christoph (Annals of plastic surgery, 2020)
Background: Surgical learning curves reflect the trainee's rate of progress in gaining skills and competence for new procedures. Complex interventions such as free tissue transfers, with various linked skills and competences, transferred to one procedure are likely to have steep learning curves. This work aimed to report influence of learning curves on outcomes such as success rate, operative time, and complication rates in plastic surgery procedures. - Methods: The study was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A systematic database literature search (PubMed, Embase, Web of Science, Cochrane Central Register of Controlled Trails) was performed. Articles were included when reporting effects of learning curves on outcomes in plastic surgery procedures. - Results: Twenty-nine articles focusing on learning curves in plastic surgery procedures were included. Studies reported on non-free flap breast reconstruction, mastectomy, and free flap reconstruction in general and for breast reconstruction and did not allow for pooling of the data because of heterogeneity. Most common outcomes for measuring improvements were success rate, operation time, and complication rate, which demonstrated improvements in almost all studies. Plateaus were reached in 45 to 100 cases for breast reconstructions and were not reported for other procedures. Only 2 studies did not find associations between surgical experience and clinical outcomes. - Conclusions: There are sparse data on learning curves in plastic surgery. Existing studies draw a heterogeneous picture, but especially free flap breast reconstructions seem to undergo learning curves with improvements in operative time, complication rates, and success rates. However, well-designed studies with clearly defined outcomes and comparison between surgeons of different levels over time should be performed. - Systematic review registration: PROSPERO: CRD42018108634
Gesehen am 08.10.2020